Associations among vegetation cover, particulate matter, and cardiovascular health in urban environments: a path analysis - Wang, Chengkang; Sun, Xuyang; Wang, Yuchong; Bai, Zherui; Kang, Lina; Xu, Biao; Jin, Jun; Cao, Jiajie; Mao, Yajing; Wei, Xuan; Liang, Huilin (Frontiers in Plant Science, 2025)
IntroductionUnderstanding the complex associative pathways linking urban green spaces to resident health is crucial for sustainable urban development and public health.MethodsThis study aimed to investigate the indirect associations between residential vegetation cover (VC) and cardiovascular health, exploring the sequential roles of particulate matter (PM) and key physiological biomarkers in a large patient cohort. Using partial least squares structural equation modeling on 32,667 patient records from Nanjing, China, we constructed a series of path models to analyze these relationships.ResultsOur findings reveal a significant indirect association between residential VC and cardiovascular health outcomes. Specifically, our path analysis reveals that higher VC is linked to lower concentrations of PM, with PM10 (particles ≤10mm) emerging as the dominant intermediary over PM2.5. In turn, lower PM10 levels are associated with healthier metabolic profiles—particularly lower total cholesterol and blood glucose levels —which were subsequently linked to better cardiovascular outcomes. Notably, total cholesterol was a key factor for reduced hospitalization frequency, while blood glucose was more strongly associated with lower incidence of heart failure. Among various vegetation metrics, Leaf Area Index demonstrated the strongest association within these pathways.DiscussionOur analysis provides evidence for a specific environmental health pathway (Vegetation → PM10 → Metabolic Biomarkers → Cardiovascular Outcomes) and highlights that vegetation quality, particularly Leaf Area Index, is a key factor. These findings offer valuable insights for urban planners and public health officials aiming to design healthier cities by leveraging the air-purifying benefits of urban green spaces.